The effect of cardiolipin side chain composition on cytochrome c protein conformation and peroxidase activity. Issue 5 (5th March 2021) - Wilkinson, Jennifer A.; Silvera, Sebastian; LeBlanc, Paul J.
Abstract: Skeletal muscle, a highly active tissue, makes up 40% of the total body weight. This tissue relies on mitochondria for ATP production, calcium homeostasis, and programed cell death. Mitochondrial phospholipid composition, namely, cardiolipin (CL), influences the functional efficiency of mitochondrial proteins, specifically cytochrome c. The interaction of CL with cytochrome c in the presence of free radicals induces structural and functional changes promoting peroxidase activity and cytochrome c release, a key event in the initiation of apoptosis. The CL acyl chain degree of saturation has been implicated in the cytochrome c to cytochrome c peroxidase transition in liposomal models. However, mitochondrial membranes are composed of differing CL acyl chain composition. Currently, it is unclear how differing CL acyl chain composition utilizing liposomes will influence the cytochrome c form and function as a peroxidase. Thus, this study examined the role of CL acyl chain saturation within liposomes broadly reflecting the relative CL composition of mitochondrial membranes from healthy and dystrophic mouse muscle on cytochrome c conformation and function. Despite no differences in protein conformation or function between healthy and dystrophic liposomes, cytochrome c's affinity to CL increased with greater unsaturation. These findings suggest that increasing CL acyl chain saturation, as implicated in muscle wasting diseases, may not influence cytochrome c transformation and function as a peroxidase but may alter its interaction with CL, potentially impacting further downstream effects. Abstract : Cardiolipin fatty acyl composition is typically polyunsaturated and is important for the interaction with cytochrome c and its dual role as both an electron shuttle and peroxidase. This study's findings suggest that increasing cardiolipin acyl chain saturation, as seen in muscle wasting diseases, may not influence cytochrome c transformation and function as a peroxidase but may alter its interaction with cardiolipin, potentially impacting further downstream effects, such as apoptosis.